1997
DOI: 10.1300/j082v32n02_03
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Coming Out Self-Efficacy for Lesbians

Abstract: The empirical literature on disclosing a lesbian sexual orientation has explored the circumstantial and demographic variables related to this act. This exploratory study utilized self-efficacy theory (Bandura, 1986) to investigate the extent to which each of the four sources of efficacy information (e.g., performance accomplishments, vicarious experience, verbal persuasion, or emotional arousal) contributed to the coming out self-efficacy of lesbians, that is, the sense of confidence possessed by a lesbian to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…With respect to gender, men had more distress associated with victimization and HIV/AIDS; this is in line with men's higher risk of LGBT-specific victimization (D'Augelli & Grossman, 2001; Herek, 2009; Herek, Gillis, & Cogan, 1999) and greater exposure to HIV/AIDS risk-related concerns (Lewis et al, 2001; Yi et al, 2010; Yi et al, 2011). Women reported greater distress associated with gender nonconformity, parenting, and vicarious trauma, which is also in accordance with the long-standing cultural relevance of gender expression in lesbian and bisexual communities (Nestle, 1992), the fact that women in same-sex relationships are more likely than men to be raising children (Solomon, Rothblum, & Balsam, 2004), and the impact of vicarious trauma on lesbian women (Anderson & Mavis, 1996). …”
Section: Discussionsupporting
confidence: 70%
“…With respect to gender, men had more distress associated with victimization and HIV/AIDS; this is in line with men's higher risk of LGBT-specific victimization (D'Augelli & Grossman, 2001; Herek, 2009; Herek, Gillis, & Cogan, 1999) and greater exposure to HIV/AIDS risk-related concerns (Lewis et al, 2001; Yi et al, 2010; Yi et al, 2011). Women reported greater distress associated with gender nonconformity, parenting, and vicarious trauma, which is also in accordance with the long-standing cultural relevance of gender expression in lesbian and bisexual communities (Nestle, 1992), the fact that women in same-sex relationships are more likely than men to be raising children (Solomon, Rothblum, & Balsam, 2004), and the impact of vicarious trauma on lesbian women (Anderson & Mavis, 1996). …”
Section: Discussionsupporting
confidence: 70%
“…However, relative importance of the sources seems to depend to a large extent upon which kind of behavior is investigated, as for example for job and coming out self-efficacy (self-efficacy for disclosing one's homosexuality), mastery experiences were less important than other sources (M.K. Anderson & Mavis, 1996;Chiles & Zorn, 1995).…”
Section: Aims Of the Current Studymentioning
confidence: 99%
“…15 Other research has found that outness among sexual minority women is associated with less anxiety, more positive affect, greater selfesteem, 16 less psychological distress, 17 higher self-efficacy, and more lifestyle satisfaction. 18 Additionally, disclosure of sexual orientation to health care providers has been associated with greater health care utilization. 6,9,19 Among lesbian and bisexual women, nondisclosure of sexual orientation to parents has been associated with greater drug abuse and depression, as well as poorer wellness behaviors in comparison to lesbian and bisexual women who have disclosed.…”
Section: Introductionmentioning
confidence: 99%